Intracranial hemorrhage after carotid artery stenting in two patients taking omega-3 fatty acids with dual antiplatelet therapy: two case reports - Farzaneh Foroughinia; Afshin Borhani-Haghighi; Elaheh Jamshidi; Haniyeh Javanmardi (Shiraz University of Medical Sciences, 2019)
Patients undergoing Carotid Artery Stenting (CAS) may encounter serious complications including Intracranial hemorrhage (ICH). ICH after carotid re-vascularization has been usually attributed to cerebral hyperperfusion syndrome (CHS) and it is reported as a significant cause of mortality and morbidity. Factors mentioned as risk factors for ICH after carotid intervention are preoperative hypertension, renal failure, bilateral carotid disease or contralateral carotid occlusion, impaired cerebrovascular reserve, female gender, age, nonselective admission, increased Charlson comorbidities score. In this study, we report two cases of ICH after CAS in patients receiving dual antiplatelet regimen plus omega-3 fatty acids before and after carotid intervention. It seems that administration of omega 3 with other antiplatelets could augment inhibition of platelet aggregation and may increase the risk of ICH in patients undergoing CAS especially in those with several risk factors for ICH. These findings are important because of the wide availability of omega-3 supplements as an over-the-counter (OTC) drug and the propensity for usage of it in alternative medicine.